ANALISIS PERILAKU KONSULTAN PAJAK UNTUK MENINGKATKAN KEPATUHAN WAJIB PAJAK - I Made Sudiartana; Kadek Apriada (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Current compliance issues are no less important because non-compliance will simultaneously lead to tax evasion efforts such as tax evasion and tax avoidance, which result in reduced tax deposits to the state treasury. The alternative that is often the choice for the Taxpayer is to use the services of tax consultants who can help the Taxpayer in exercising the rights and fulfill his obligations in the field of taxation, tax consultant is of course important in tax structure, because tax consultant is an extension of the Directorate General of Taxes in socializing issues taxation to Taxpayers. This study aims to determine the effect of tax consultant behavior to improve taxpayer compliance, which consists of: code of ethics, professionalism, machiavellian nature. The research was conducted at Tax Consultant Office (KKP) in Denpasar which registered at Ikatan Konsultan Pajak Indonesia (IKPI). Data collection was done by distributing questionnaires with sample number 97 Tax Consultant in Denpasar registered in IKPI Denpasar.Teknik data analysis used is the validity test and reliability; classical assumption test which includes normality test, heteroscedasticity test, and multicollinearity test, multiple linear regression analysis using SPSS 16for windows. Based on the results of the research discussed that the code of ethics has a positive effect on tax compliance, while professionalism, and the nature of machiavellisnot affect the compliance of Taxpayers.